Locational investment signals - How to steer the siting of new generation capacity in power systems? - Anselm Eicke; Tarun Khanna; Lion Hirth (The Energy Journal, 2020)
New generators located far from consumption centers require transmission infrastructure and increase network losses. The primary objective of this paper is to study signals that affect the location of generation investment. Such signals result from the electricity market itself and from additional regulatory instruments. We cluster them into five groups: locational electricity markets, deep grid connection charges, grid usage charges, capacity mechanisms, and renewable energy support schemes. We review the use of instruments in twelve major power systems and discuss relevant properties, including a quantitative estimate of their strength. We find that most systems use multiple instruments in parallel, and none of the identified instruments prevails. The signals vary between locations by up to 20 EUR per MWh. Such a difference is significant when compared to the levelized costs of combined cycle plants of 64-72 EUR per MWh in Europe.
Keywords: Q48; Q41; L51; L10; 330; Electricity markets; Incentive regulation; Locational signals; Generation investment